Metode Pembelajaran Bahasa Arab Berdasarkan Pendekatan Komunikatif Untuk Meningkatkan Kecakapan Berbahasa - Gilda; Tatang; Hikmah Maulani (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
Communicative approach is a language learning approach that emphasizes the assignment of language skills rather than language structure. This study aims to describe the effectiveness of language using a communicative approach through various learning methods in Arabic language learning to improve language skills, the method used is to use the literature study method or also called the literature study method whose data comes from various sources of literature relevant to this research, the subject of this research is MI and MTS Ar-Rohmah students, then the data collection techniques that researchers choose are, interviews, observation and documentation.  The results of this study also show that learning methods using communicative methods are very influential to support language skills. the role of the teacher, and the teaching materials used are also very important in the teaching and learning process.